Implementasi Dashboard Monitoring Laju Pertumbuhan Penduduk di Rukun Warga 011 Pondok Kelapa Menggunakan Tableau Public - Tri Wahyudi; Melinius Nopianto; Julia Rani; Dandi Rizki Kurniawan; Denny Nugraha (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
The purpose of this outreach is to assist the Pondok Kelapa 11 Residential Pillars community in monitoring population growth and trends. As the pandemic situation impacts municipal population growth, the service implements a tableau-based monitoring dashboard to facilitate monitoring of population trends. When collecting data, qualitative techniques are used to ensure the accuracy of the information received, with a focus on data collection, processing, and development. During the discussion, the data processing results of the population growth rate from January to October 2022 received by the Rukun Warga 11 Secretariat were presented. Through this community service, it is hoped that the community of RW 11 Pondok Kelapa will be able to visualize data more easily and accurately on population growth while raising awareness of the importance of monitoring population growth in community organizations.